Valuation in Multifinance Acquisition by Bank MDR: A Case Study - Jiwo Sukarno; Tedy Fardiansyah (Journal of Applied Finance & Accounting, 2009)
Bank MDR as one of leading banks in Indonesia, aims to capture 20 to 30% of revenue share in each of their businesses, including Consumer Finance. One crucial sub-segment in Consumer Finance Business is Automotive Loan, which currently dominated by Multifinance companies. To increase the pace of becoming dominant in Automotive Loan, ”inorganic initiatives” are required to supplement the organic efforts to grow the revenue shares of Bank MDR. In early 2009, Bank MDR engages in inorganic investment by acquiring a multifinance company, Tunas Finance. The main purpose of this study is to examine an alternative approach to value an acquisition of a multifinance company, as well as to observe whether the acquisition done by Bank MDR is creating value for its shareholders. Valuation of an acquisition is not fundamentally different from valuation of any firm, however, valuing a multifinance company poses particular challenges. Given that Bank MDR has announced that it would pay 290 billion rupiahs for 51% shares of Tunas Finance, this study, following Excess Return Model Valuation (Damodaran, 2002), shows results that acquirer shareholders still earn positive value from the acquisition.